What Are the Benefits of AI-Assisted Minimally Invasive Surgery? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2018)
The integration of artificial intelligence (AI) into the surgical field, particularly in minimally invasive surgery (MIS), represents a significant paradigm ...
Keywords: AI in Surgery and Robotics; Benefits; AI-Assisted; Minimally; Artificial Intelligence; Deep Learning; Healthcare